2017
DOI: 10.1016/j.cej.2017.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism identification of temperature influence on mercury adsorption capacity of different halides modified bio-chars

Abstract: Bio-chars as mercury sorbent were derived from cotton straw via pyrolysis carbonization, microwave/steam activation and ammonium halides impregnation. Mercury adsorption capacity of various impregnated bio-chars was tested at different temperatures. Rising temperature improved the adsorption capacity of bio-chars modified with NH 4 Br and NH 4 I yet inhabited that of bio-char modified with NH 4 Cl. Kinetic model analysis indicated that the changes of mercury adsorption capacity were related to the difference o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 36 publications
(49 reference statements)
0
23
0
Order By: Relevance
“…Among the numerous removal techniques, heterogeneous adsorption is currently the most effective method and has been extensively studied . When optimizing the performance of adsorbents, researchers first focus on the adsorption capacity, stability, and selectivity of the material. However, the presence of other atmospheres in the flue gas, such as sulfur dioxide (SO 2 ), and large fluctuations in temperature are still a challenge for the adsorption of Hg 0 . …”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous removal techniques, heterogeneous adsorption is currently the most effective method and has been extensively studied . When optimizing the performance of adsorbents, researchers first focus on the adsorption capacity, stability, and selectivity of the material. However, the presence of other atmospheres in the flue gas, such as sulfur dioxide (SO 2 ), and large fluctuations in temperature are still a challenge for the adsorption of Hg 0 . …”
Section: Introductionmentioning
confidence: 99%
“…Using separate equipment to control Hg 0 and AsH 3 could result in larger capital investments for equipment, higher operation costs, and other possible problems related to process complexity. In previous studies, metal oxide catalysts and halide modified sorbents have been reported to have high activity for both Hg 0 and AsH 3 removal separately, ,, but these studies rarely combined the metal oxides and halide. Furthermore, studies have been carried out using gases with an oxygen content of 8–10% in N 2 , , but examples of removing contaminants from a reducing atmosphere (approximately 80% CO) under low temperature and micro-oxygen conditions (1%) have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…17 Sorbents modified using halides (such as Cl, Br, I) have also been widely used to control mercury emissions. 20,21 For example, Li et al 22 have reported considerable enhancement in the removal of mercury over halide modified biochars. Also, Shen et al 23 studied the removal of Hg 0 by an NH 4 Cl impregnated sorbent.…”
Section: Introductionmentioning
confidence: 99%
“…It is inferred that, during the mechanical milling process, the unburned carbon on the fly ash surface reacts with NaBr crystal, which promotes the formation of CBr covalent group and is consistent with the result of no characteristic peak of NaBr observed in XRD patterns. It has shown that the CBr covalent group is the main chemisorption site of Hg 0 , which determines the mercury adsorption capacity of the modified adsorbent …”
Section: Results and Discussionmentioning
confidence: 99%